2007
DOI: 10.5194/aab-50-575-2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding on the composition of longissmus muscle of Hungarian Grey and Holstein Friesian bulls. – III. Amino acid composition and mineral content

Abstract: In this experiment the effect of the extensive diet (grass/grass silage and concentrate linseed supplemented) versus intensive diet (maize silage and concentrate) on the amino acid composition and mineral content of Hungarian Grey and Hungarian Holstein Friesian young bulls was analysed. In addition the relationships between fatty acid profile and amino acid composition as well as mineral content of longissimus muscle were investigated. The extensive diet caused some changes in the proportion of some amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
0
27
1
Order By: Relevance
“…This agrees with the knowledge from Subrt et al (2002), who also found significant differences in a number of EAAs and NEAAs. Hollo et al (2007) state that an extensive diet with grass/grass silage and concentrate with linseed supplements caused changes in the proportion of some amino acids compared to that of intensive groups. The enhancement of the Phe, Val, Pro, and ammonia concentrations and the decrease of Ile, Leu, Thr, Cys, Gly, and Ser were observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This agrees with the knowledge from Subrt et al (2002), who also found significant differences in a number of EAAs and NEAAs. Hollo et al (2007) state that an extensive diet with grass/grass silage and concentrate with linseed supplements caused changes in the proportion of some amino acids compared to that of intensive groups. The enhancement of the Phe, Val, Pro, and ammonia concentrations and the decrease of Ile, Leu, Thr, Cys, Gly, and Ser were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Breed differences were detected only for the His concentration of the musculus longissimus. The meat cattle that we monitored were bred solely in the extensive method and the differences between individual AAs in connection with intensive diet, as stated by Hollo et al (2007), could not be found. However, we also found significant differences between the monitored breeds in the musculus longissimus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…GERBER and co-workers (2009) emphasize that the exact mineral content of meat is important to know, the evaluation of the nutritive value without this is unpredictable, so the calculated human nutrition recommendations may not be accurate. According to the literature, the concentration of mineral elements of beef is affected by animal age (SCHÖNFELDT & GIBSON, 2008), breed (CABRERA et al, 2010), gender (LÓPEZ-ALONSO et al, 2000), muscle type (PURCHAS & BUSHBOOM, 2005;CABRERA et al, 2010), feeding system (HOLLÓ et al, 2007), and cooking and processing methods (LOMBARDI-BOCCIA et al, 2005). According to the studies, the concentrations of minerals differ in the different muscles.…”
mentioning
confidence: 99%